TRANSITION PLAN TOWARDS AN INCLUSIVE SCHOOL: A CASE STUDY OF SDN 3 TUNJUNGAN BLORA 2025 – 2030 - Dwinanto Dwinanto; Liftiah Liftiah; Ali Formen (Universitas Muria Kudus, 2026)
This article presents a comprehensive five-year inclusive school transition plan (2025–2030) for SDN 3 Tunjungan, Blora Regency, Central Java. A qualitative approach with a single case study design was employed. Data were collected through document analysis, participatory observation, and semi-structured in-depth interviews with eight informants: the principal, teachers, parents of children with special needs, and a district education supervisor. Data analysis followed the Miles, Huberman, and Saldaña (2014) model, with validity ensured through source and method triangulation. SDN 3 Tunjungan possesses significant social capital to support transition, including community-based solidarity values, adaptive school leadership, and strong parental engagement traditions. The transition plan is structured into five spiral stages: (1) foundation and awareness-building, (2) system and infrastructure development, (3) full Universal Design for Learning implementation, (4) consolidation and external validation, and (5) policy institutionalization. Six sustainability pillars were identified: policy embedding, continuous teacher capacity development, diversified funding, inclusive school culture, strategic partnerships, and public accountability monitoring. This study contributes a contextual inclusive transition model adaptable by public elementary schools in rural Indonesia. The practical implication of this study is that schools can replicate this spiral transition model by leveraging existing social capital, securing multi-source funding, and establishing institutional policies that sustain inclusive education beyond individual leadership cycles.